Fundamental thinking terms in the qur’ān: a connotative analytical framework for Islamic epistemology - Badi, Jamal Ahmed Bashier (ISTAC, IIUM, 2025)
Al-Shajarah: Journal of the International Institute of Islamic Thought and Civilisation, International Islamic University Malaysia (ISTAC-IIUM) https://journals.iium.edu.my/shajarah/index.php/shaj 313 Vol. No.: 30 Issue No.: 2 (2025) Page No.: 313-354 DOI: 10.31436/shajarah.v30i02.2169 FUNDAMENTAL THINKING TERMS IN THE QUR’ĀN: A CONNOTATIVE ANALYTICAL FRAMEWORK FOR ISLAMIC EPISTEMOLOGY Jamal Ahmed Bashier Badi1 ABSTRACT This study addresses a significant scholarly gap concerning a lack of a comprehensive framework for systematically examining the connotative dimensions of fundamental Qurʾānic terms related to thinking (tafakkur, taʿaqqul, tadabbur, tafaqquh) and knowledge (ʿilm, maʿrifah). While the presence and importance of these terms in Qurʾān are widely acknowledged, existing scholarship has tended to prioritise their denotative or literal meanings, often focusing on a restricted subset of these terms, particularly those associated with Qurʾānic epistemological discussions. As a result, insufficient attention has been given to the contextual and connotative significance of these terms and to how their deeper semantic layers articulate the Qurʾān’s holistic worldview of thinking and knowledge. Consequently, this study proposes an innovative connotative analytical framework that categorises Qurʾānic thinking terms into four distinct semantic dimensions. It employs a qualitative method of textual analysis, drawing upon classical and contemporary Qurʾānic tafsīr literature, alongside studies on Qur’anic terminology (muṣṭalaḥāt Qurʾāniyyah), as its primary sources of data. The study demonstrates that a connotative and contextual interpretation of these terms reveals the dynamic, multi-layered, and holistic system of thought that characterises the Qurʾānic approach to human cognition and epistemology. Overall, it provides a comprehensive overview of these terms as foundational building blocks of an Islamic holistic epistemological framework of thinking and knowledge.